An Analysis of Wahbah Az-Zuhaili's Views on Interfaith Marriage and Its Implementation in Indonesian Legal Context - Abdullah, Arifin; Amri, Aulil; Nadia, Varatun; Khalidi, Muhadi (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
Marriage is a very important need in family and a social life that is pleasing to Allah, therefore in choosing a husband and wife, Islam strongly recommends that everything be based on religious norms so that the life companion has commendable morals, there is no balance to a belief. However, the problem is that it is forbidden for Muslim men to marry polytheistic women and marriage between Muslim women and infidel men. Meanwhile, Wahbah Az-Zuhaili's opinion that Muslim men and women are different from the opinions of other scholars. This research is with the formulation of the problem: How does Wahbah Az-Zuhaili think about interfaith marriage and how is the review of Islamic law about interfaith marriage in Islamic law thinking according to Wahbah Az-Zuhaili. This research is a type of library research. whose research object is the opinion and legal istinbath used by Wahbah Az-Zuhaili. The data collection method of this research uses a method of collecting legal materials, journals, and so on. The data analysis is qualitative, that is, the analysis is carried out by grouping data, presenting the results of the analysis in the form of a narrative, and drawing conclusions. Based on the results of this study, Wahbah Az-Zuhaili knew that it is forbidden to marry a Muslim man to a polytheistic woman, interfaith marriage, a Muslim woman to an infidel man, marriage between a Muslim man and a woman who is an expert in the book. The legal identity used by Wahbah Az-Zuhaili himself is QS. Al-Baqarah Al-Mumtahanah Al-Maidah. But the woman whose books are referred to is only the descendants of the children of Israel who still hold fast to the original book that was handed down to the Prophet Moses and the Prophet Jesus AS. As a defect, the prophets Moses and Jesus were sent only for the Bani Israel.